A Simplified Technique for Fabrication of One Piece Closed Hollow Bulb Obturator for Rehabilitating Young Adult with Total Maxillectomy: A Clinical Report - Dhital, Shaishab; Mathema, S. (Journal of Nepalese Prosthodontic Society, 2018)
Rehabilitation of patients with a palatal defect requires management of anatomical, functional, esthetics as well as psychological factors. A reduced denture-bearing area, increased inter arch space, and cantilever movement cause complex problems in these palatal defects. Solid obturator is heavy and continuous stresses on the remaining tissues jeopardizes the health, compromise the function of the prosthesis and affect patient comfort. Reducing the weight of the prosthesis by making it hollow prevents the cantilever movement thereby increasing retention, stability and brings improvement in speech by resonance effect. This clinical report describes the rehabilitation of young adult patient with total maxillectomy using maxillary hollow bulb obturator fabricated with lost salt technique.